Cognitive processes and Psycholinguistic strategies involved in reading comprehension: design and implementation of a experimental program for children with learning problems - Canales G., Ricardo (2008)
The investigation shows the results founded in the field of Reading Comprehension. Starting from the theoretic model of cognitive psychology and psycholinguistics, and in particular the theory of Van Dijk and Kintsch (1983, 1993, 1994). The author explores the problematic of comprehensive reading in a group of children and teenagers with learning disabilities in the province of Callao, trying to know how much can they could intervening in the improvement of their reading weakness, for what we have design and application and an Experimental Program of Treatment. The most important idea of the study was the significant difference in reading comprehension levels reached in the pre test and in the post test, by the group I students after applying the experimental program, and as an important improvement in the student group II.